38 Does interaction between peroxisome proliferator-activated receptor-α and NADPH oxidases play an important role in regulating pressure-overload cardiac hypertrophy?. Issue 20 (23rd September 2011) - Harvey, A P; Robinson, E; McDermott, B J; Grieve, D J
Abstract : Activation of NADPH oxidases and deactivation of peroxisome proliferator-activated receptor-α (PPAR-α) are known individually to play key roles in the development of left ventricular hypertrophy (LVH). Interestingly, it appears that interaction between the two may influence overall regulation of LVH and this was the focus of our study. Nox2KO, PPAR-αKO and matched wild-type (WT) mice (n>8) underwent thoracic aortic constriction (TAC) or sham surgery and were studied 7 days later. TAC-induced increases in LV/body weight in WT mice (10.8%±2.1%) were attenuated in both PPAR-αKO and Nox2KO mice (1.6±1.8 and 1.7±3.0%, respectively; p<0.05 vs WT). However, echocardiography indicated that TAC-induced decreases in fractional shortening in WT mice (−15.6%±2.1%) were augmented in PPAR-αKO mice (−28.0%±3.8%; p<0.05 vs WT), but were unaltered in Nox2KO mice (−9.7%±3.4%). Interestingly, these structural and functional changes were associated with differential activation of Nox2 and PPAR-α. Increases in PPAR-α mRNA expression (real-time RT-PCR) observed in WT TAC vs sham mice (1.31±0.08 vs 1.01±0.05 arbitrary units; p<0.05) were reversed in Nox2KO mice (0.83±0.11 vs 1.11±0.10; p<0.05), while parallel reductions in Nox2 mRNA expression in WT mice (0.49±0.03 vs 1.03±0.09; p<0.05) were not evident in PPAR-αKO mice. Furthermore, in LV cardiomyocytes from WT mice, both basal (54.2±12.0 vs 28.6±5.4 relative light units; p<0.05) and H2 O2 -stimulated (62.3±17.3 vs 32.3±6.3; p<0.05) NADPH oxidase activity (lucigenin-enhanced chemiluminescence) was reduced by the PPAR-α activator, fenofibrate. Taken together, these data indicate that PPAR-α and NADPH oxidases may interact during development of pressure-overload LVH, although the precise nature of their relationship appears to be complex.